Public Support for Policies Addressing Contaminated Sites: Evidence From a Survey of the Italian Public - Anna Alberini; Aline Chiabai; Margherita Turvani; Stefania Tonin (European Regional Science Association (ERSA), 2006)
Cleaning up contaminated sites is currently considered one of the most environmental policy priorities in many countries. Remediation of contaminated sites is attractive because it reduces risks to human health and ecological systems, and brings a host of potential social and economic benefits, because contaminated areas are often found in urban areas where the majority of Europe's population resides. Yet, cleaning up is a costly and time consuming effort, and its benefits are incurred primarily in the future. Large costs are on public finance and in this paper we offer preliminary results of a survey conducted in 2005 in Italy (800 people). We address issues of people's awareness of the problems related to contaminated sites, including their perceptions are about the health risks associated with contaminated site exposures, and an assessment of public's preferences regarding various policies currently being considered in Italy and the European Commission .
Keywords: 330